Solid papillary carcinoma of the breast: A special entity needs to be distinguished from conventional invasive carcinoma avoiding over-treatment. (April 2016) - Guo, Shuangping; Wang, Yingmei; Rohr, Joseph; Fan, Chaoliang; Li, Qinglong; Li, Xia; Wang, Zhe
Abstract: Introduction: Solid papillary carcinoma of the breast, a newly-defined entity, is poorly recognized, and its nature and management is still debated. Material and methods: Eleven cases of pure solid papillary breast carcinoma in our archive and 253 cases reported in previous literature were retrospectively analyzed for their clinicopathological features and outcomes. Results: The eleven cases occurred in elderly females. Grossly, all tumors were well-circumscribed and typically composed of solid papillary nodules. The tumor cells were bland-looking with low-grade atypia and mitoses < 5/10HPF. Immunophenotypically, all eleven cases showed positivity for ER and PR, negativity for CK5/6 and HER2, and a low proliferative index of Ki67. Five cases showed scattered positivity for myoepithelial marker p63, and four cases were positive for CK5/6 and CD10 around the nodules, whereas the other cases were completely negative for all myoepithelial markers. Five cases expressed the neuroendocrine marker synaptophysin, and six cases expressed chromogranin. In nine cases, mastectomy and axillary lymph nodes excision were performed, and only one showed micrometastasis in an axillary lymph node. There was no local recurrence or distant metastasis or breast carcinoma related-death during the follow-up periods of 50 months. Out of 253 solid papillary breast carcinomas reported in literature, the percentage of axillary lymph node metastasis was 4/136 (3%), with rare local recurrences and distant metastasis; only three patients died of breast carcinoma. Conclusion: Solid papillary carcinoma of the breast is a rare entity with distinctive clinicopathological features and excellent prognosis and should be distinguished from conventional breast carcinoma to avoid over-treatment.